The Effect Of Tele Education On Knowledge And Attitudes About HIV/AIDS Prevention In Students At Cut Nyak Dhien Langsa Unggul High School In 2022 - Sumarni, Eli; Sinaga, Lia Rossa Veronika; Manurung, Kesaktian (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2022)
According to the World Health Organization (WHO) HIV continues to be a major global public health problem. There are an estimated 38 million people living with HIV at the end of 2019. As a result of concerted international efforts to respond to HIV, service coverage continues to increase. In 2019, 68% of adults and 53% of children living with HIV globally were receiving antiretroviral therapy. In 2019, 68% of adults and 53% of children living with HIV globally were receiving lifelong antiretroviral therapy (ART), yet 7.1 million people living with HIV did not know they had HIV. And because of gaps in HIV services, 690,000 people died from HIV-related causes in 2019 and 1.7 million people were newly infected (WHO, 2020.). This study used a quasi-experimental method with a pre-test and post-test one group only design. Samples were taken as many as 33 people. Data collection was carried out using a questionnaire. Sampling was carried out using the Total Sampling method. The results of the study using Paired t-test obtained P-Value 0.000 there was a significant difference in the average increase in knowledge scores about HIV/AIDS prevention where the average knowledge of students before tele education was 8.636 and the average student/I after tele education was 12,424 so that the difference between changes before and after tele education was 3,788, where the average attitude of students before tele education was 49,697 and the average student/I after tele education was 62,030 so that the difference between changes before and after tele education is 12,333. It is hoped that health promotion efforts for students are carried out more creatively by using different media as an effort to increase students' knowledge and attitudes as primary prevention in adolescents.